2024
DOI: 10.1109/tem.2022.3185626
|View full text |Cite
|
Sign up to set email alerts
|

Information Elaboration and Coopetition: Participation in the Replacement of Legacy Systems

Abstract: Legacy information system (LIS) replacement projects are increasingly complex. Consequently, they require cooperation to integrate different functional knowledge to support organizational business processes. However, cooperation on crossfunctional LIS replacement project teams face inherent competition for scarce resources and conflicting functional interests. The common assertion is to reduce or eliminate this competition. We suggest that the potential benefits of competition complement the known benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 107 publications
(255 reference statements)
0
2
0
Order By: Relevance
“…Even before the popularity of agile approaches, wisdom and research indicated that user participation in IT projects is essential for success (Jiang et al, 2002; Liu et al, 2010). Participation ranges from simple tasks such as user reviews up to equal responsibilities (Hsu et al, 2010; Shim et al, 2010; Tsai et al, 2022b). Securing participation can prove more difficult than realizing the benefits of participation.…”
Section: Careers Consumers and Consonancementioning
confidence: 99%
“…Even before the popularity of agile approaches, wisdom and research indicated that user participation in IT projects is essential for success (Jiang et al, 2002; Liu et al, 2010). Participation ranges from simple tasks such as user reviews up to equal responsibilities (Hsu et al, 2010; Shim et al, 2010; Tsai et al, 2022b). Securing participation can prove more difficult than realizing the benefits of participation.…”
Section: Careers Consumers and Consonancementioning
confidence: 99%
“…In MTS, teams often learn from failure when resolving cognitive conflicts (Gu et al, 2013; Madsen & Desai, 2010; Wilhelm et al, 2019). However, in an MTS, skill-based differences can make it challenging to resolve conflicts cooperatively, especially when untested knowledge is being challenged (Firth et al, 2015; Shuffler & Carter, 2018; Tsai et al, 2022b; Zaccaro et al, 2012). Observing others’ failures can lead to new insights, but only if a team operates within formalized routines (Bresman, 2010; Gu et al, 2013; Wilhelm et al, 2019).…”
Section: Introductionmentioning
confidence: 99%